ANALISIS USAHATANI PADI: (STUDI KASUS DI DESA BELANTI SIAM, KECAMATAN PANDIH BATU, KABUPATEN PULANG PISAU): Analysis of Rice Farming: (Case study in Belanti Siam Village, Pandih Batu District, Pulang Pisau Regency - Revi Sunaryati; Fandi Karuniawan Putra Asiaka; Ellydia Ludang (AgriPeat, 2022)
This study aims to determine the description of farming and to analyze the income of Rawa Paddy and its contribution to the household income of farmers in Belanti Siam Village, Pandih Batu District, Pulang Pisau Regency. The data analysis method uses a combination of primary and secondary data. The data obtained from the results of research and are qualitative in nature are processed in tabulated form and edited in the form of explanatory descriptions of the results of the interviews. The data from the research were then analyzed according to the purpose of this study. The sample of this research is Farmer Households (RTP) who have a steady income from Rawa Paddy Farming, where there are two farmer groups of 20 people and 22 people, then a random sample is taken from the 2 groups. The results of this study indicate that the income of Rawa Paddy obtained by farmers is Rp. 36,355,109 for one year and contributes 74.93% of the total household income of farmers of Rp. 48,518,176, or an average of Rp. 4,043,181 per month. . In general, it can be said that the income of Rawa Padi is quite large when compared to the minimum wage of Pulang Pisau Regency of Rp. 2.4 million per month, this shows that the role of swamp rice farming for farmers in Belanti Siam Village is very positive because it can increase farmers' income